The interplay between foreignization of dish name and interactive meaning of visual image in food documentary - Zhang, Qi; Ang, Lay Hoon; Yasin, Megat Al Imran (Human Resource Management Academic Research Society, 2022)
A Bite of China 1, a popular food documentary with numerous food-related culture-specific items and including the interplay between subtitles and visual images, is selected as the data to be examined in this study. The purposes of this study are firstly to identify foreignization strategy in the translation of dish names based on Aixela’s model, and secondly to explore the interplay between visual images and foreignization, so as to demonstrate how visual images help to make up for the loss caused by foreignization and further facilitate the understanding of Chinese dishes and culture. Purposive sampling is employed to collect data and 112 samples on dish names with corresponding images are obtained. The findings reveal that transliteration, linguistic translation and intratextual gloss under the category of foreignization are three main translation strategies when rendering Chinese dish names into English. Apart from foreignization affecting the meaning conveyance of dish names, the results also suggest that interactive meanings of visual images play a vital role in facilitating target audiences’ understanding of Chinese dish names by providing detailed background information, whereas the connotative meanings behind Chinese dish names cannot or can hardly be obtained through the visual images or translation alone.